2021
DOI: 10.31234/osf.io/57pwf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk, Trust, and Flawed Assumptions: Vaccine Hesitancy During the COVID-19 Pandemic

Abstract: Background: The pace at which the present pandemic and future public health crises involving viral infections are eradicated heavily depends on the availability and routine implementation of vaccines. This process is further affected by a willingness to vaccinate, embedded in the phenomenon of vaccine hesitancy. The World Health Organization has listed vaccine hesitancy among the greatest threats to global health, calling for research to identify the factors associated with this phenomenon. Methods: The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…However, it is worth noting that these studies were conducted when the COVID-19 vaccination campaign had not started. One study from Norway found a hesitancy rate close to our study in January 2021 (10.5%) (26).…”
Section: Discussionsupporting
confidence: 82%
“…However, it is worth noting that these studies were conducted when the COVID-19 vaccination campaign had not started. One study from Norway found a hesitancy rate close to our study in January 2021 (10.5%) (26).…”
Section: Discussionsupporting
confidence: 82%
“…Several studies conducted in different countries have demonstrated that trust in the vaccine and in governmental health authorities are strongly related to acceptance of the COVID-19 vaccination ( Ebrahimi, et al, 2021 ; Jennings, et al, 2021 ; Konstantinou, et al, 2021 ; Lamot, Krecic, & Kirbiš, 2021 ; Park, Ham, Jang, Lee, & Jang, 2021 ; Szilagyi, et al, 2021 ). These studies show that trust in the safety and effectiveness and the importance of getting vaccinated reflect trust in the authorities.…”
Section: Discussionmentioning
confidence: 99%
“…As household income is related to education, level of education may influence individuals’ knowledge and perceptions regarding COVID-19 vaccines [5]. Both education level and its associated assumptions of knowledge and perceptions may contribute to vaccination hesitancy among those with limited health literacy or with mistrust in science and health agencies [35]. Additionally, a significant finding is that although the COVID-19 vaccine was administered at no cost to all people in the United States, those who are uninsured were associated with low vaccination uptake.…”
Section: Discussionmentioning
confidence: 99%
“…As household income is related to education, level of education may influence individuals' knowledge and perceptions regarding COVID-19 vaccines [5]. Both education level and its associated assumptions of knowledge and perceptions may contribute to vaccination hesitancy among those with limited health literacy or with mistrust in science and health agencies [35].…”
Section: Discussionmentioning
confidence: 99%